Preparation and characterization of dual layer lanthanum strontium cobalt ferrite/alumina hollow fibre membrane - Abdullah, Norfazliana (2016)
Ceramic membrane with unique morphology can be prepared using phase inversion and sintering technique. Dual layer lanthanum strontium cobalt ferrite (LSCF)/alumina hollow fibre membrane in this study was prepared using this technique. The contributing parameters in the preparation of asymmetric alumina hollow fibre during fabrication process were investigated. The parameters involved in the process were the alumina/polyethersulfone (PESf) ratio, the internal coagulant temperature and the air-gap distance. Next, the suitable LSCF coating formulations were studied to obtain thin layer of LSCF. This was followed by the impregnations of catalyst prepared using sol-gel Pechini method. The characterizations were carried out for scanning electron microscopy (SEM), energy dispersive X-Ray spectrometry (EDX), apparent porosity, gas permeability test, gas-tightness test, Brunauer–Emmett–Teller technique, dilatometer analysis and mechanical test. The results showed that a reduction of alumina/PESf ratio from 10 to 6 resulted in the formation of asymmetric structure. The 53 weight % of alumina (AL-53) was selected as membrane support with 1.68 mm, 1.08 mm and 168 µm of outside, inside diameter and finger-like length, respectively. The AL-53 had acceptable mechanical strength of 24 MPa and high gas permeability of 13.87 x 10-4 mol m-2 Pa-1 s-1. The 25 weight % of LSCF membrane sintered at 1150 oC had the lowest nitrogen gas permeability of 2.401 x 10-6 mol m-2 Pa-1 s-1 that was considered as gas-tight LSCF layer. The dual layer LSCF/alumina hollow fibre membrane was impregnated with 10 weight % of cerium oxide doped copper oxide catalyst. This catalyst was characterized using the SEM/EDX to ensure the catalyst was placed inside the finger-like structure of alumina membrane support. The dual layer of LSCF/alumina hollow fibre membrane was successfully produced using phase inversion and sintering technique which will be beneficial for multifunctional applications.